ANALISIS BIAYA DAN PENDAPATAN PETERNAK AYAM BROILER DI KOTA SEMARANG - Dwi Umi Mulyaningsih; W D Prastiwi; W Sarengat (Universitas Wahid Hasyim, 2019)
ABSTRACT The research intends to know the cost and income broiler breeders in Semarang City. Reasearch obtained by breeders in Gunungpati district and Mijen district. The method use in this research is survey method with purposive sampling method. The study look place from January until February 2015. Data collection consisted of primary and secondary data. Primary data obtained from the observation and interviews of respondents. The results of this study show calculation there is no difference in cost and income between broiler breeders in Gunungpati district with Mijen district. The results show that the average cost of broiler breeders in Gunungpati district Rp 198.003.520,04 and in Mijen district Rp 183.488.974,87 and the average income of broiler breeders in Gunungpati district Rp 14.422.095 and in Mijen district Rp 17.209.832. There is no difference in cost broiler breeders in Gunungpati district and Mijen district with significance value 0,627>0,05, and there is no difference in income broiler breeders in Gunungpati district and Mijen district with significance 0,653>0,05. Keywords: Broiler chicken, cost, income, breeders.